La Torna o el pols a la dictadura cuejant - Toda i Bonet, Agnès (Studia Romanica Posnaniensia, 2015)
This article analyses the terrorism that can be found in La Torna – the terrorism included in the work as much as the terrorism that the play itself is a victim of – in order to realize what is looked for and achieved in both cases. This study considers two major issues. On the one hand, it gives an account of the dynamic resistance of Els Joglars (the company which performed La Torna) in response to the brutal dictatorship of the Spanish state (1939-1975), objectified in the particular case of Heinz Chez’s murder. On the other hand, it looks at what the State’s repression – which survived the dictatorship’s end – represents (Franco died in 1975, and this work was first presented in 1977). This repression probably gives the play and its content a greater impact than it might have had by itself. Moreover, this repression shows that the dictatorship goes beyond the dictator’s death, troubling the population that aimed to recover from that historical period.